Analysis of bisphenol-propane in dialyzer and its effect on human body - Yun, Chen; He, Xiaofan; Xie, Ting; Chi-Wa, Ao-Ieong; Li, Weilong; Song, Zhuoheng; Xiao, Mengyun; Meng, Yu; Hu, Bo; Guan, Baozhang; Yang, Lifeng; Ye, Mingjun; et al. (Materials express, 2023)
The effect of trace solvent bisphenol A (BPA) in polyether sulfone hollow fiber membrane Enttex™-16LF (E60) (produced by 3 M) low-throughput dialyzer was tested in this study. Animal experiments were conducted to evaluate its genotoxicity, carcinogenicity, and teratogenicity upon - chronic exposure. The dialyzer was operated at 200 mL/min and 400 mL/min and coupled with LC-20AT liquid chromatography to detect BPA, which showed that the BPA content was less than 5 μg/kg/d at both flow rates. In animal experiments, the tolerable intake (T.I.) was calculated to - be 0.5 μg/kg/d. With hemodialysis three times per week, the average patient weight was calculated at 70 kg, and the average daily BPA exposure was 0.0306 μg/kg/d. The risk of residual BPA was within the acceptable limit with polyether sulfone membrane Enttex™-16LF - (E60) hollow fiber dialyzer from 3 M, without inducing risk for disability, teratogenicity, or genotoxicity.